Attitude of Midwifery Students Regarding the Comprehensive Exam of Ardabil School of Nursing and Midwifery - Shiva Jegargoosheh (Babol University of Medical Sciences, 2021)
Background and Objective: Holding a comprehensive midwifery exam is one of the main concerns of midwifery students and if they do not get a sufficient score, their midwifery qualification will not be approved. The aim of this study was to investigate the opinions of midwifery students about the comprehensive exam of Ardabil School of Nursing and Midwifery. Methods: In this descriptive cross-sectional study, 58 undergraduate midwifery students were enrolled in the study in September 2018. Students' opinions in 5 clinical areas of labor, delivery, postpartum, gynecological clinic and pediatric clinic were collected through a questionnaire one day after evaluation. The results of the data were analyzed using descriptive statistics (frequency-percentage and mean standard deviation). Findings: Students' opinions on how to evaluate with mean and standard deviation of 78.91 ± 13/81were at the desired level. Mean and standard deviation of gynecological clinic opinions 82.51 ± 12.37, Mother-Child Clinic 80/46 ± 12/62, Liber 79/48 ± 13/12, After delivery 77/12 ± 15/23 And delivery room was 75.02 ± 15.73 out of a total score of 100. Conclusion: The opinions of midwifery students about the comprehensive exam of Ardabil School of Nursing and Midwifery are at the desired level. In addition to continuing the existing programs to improve the exam conditions and how to take the exam, other evaluation methods should be considered.